Leitura digital e sentidos - Santos, Luciene Oliveira da Costa (2017)
The several forms of communicating in hypermedia atmospheres acquire a suc relevance that show the all is present the need to grow more researches in that extent. Before that, this work goes back to the reading in net atmosphere and the study on the coherence in hypertexts, without forgetting the fact is inserted in the daily of the subjects. The objectives of this theory are shown in to investigate the reading in the hypermedia atmosphere and to contemplate on the coherence for construction of senses in that support, considering the specific aspects of the hypertexts. Starting from the observation of fragments of a portal of news of the internet, this work presents exemplified definitions of the coherence in the hypertext. The theoretical contribution feels in the Dascal (2006), Elias (2011), Hilgert (2005), Koch (2005, 2007, 2008), Koch and Travaglia (2008), Koch and Elias (2011) Marcuschi (2012, 2007), Van Dijk (2012) and others. There is prominence for the notions that the coherence of a text is a construction that demands some aspects as intelligibility and interpretable (KOCH; TRAVAGLIA, 2008 and that not just the linguistic knowledge are important in the coherence, but also the reader’s other knowledge as encyclopedic (work knowledge kept in the memory) knowledge, knowledge of text (to activate preexistent models), knowledge interactional (to activate the practices) (KOCH; ELIAS, 2011), because it in mainly in the widest extent of the text than shows in the structuring of senses (MARCUSCHI, 2012). The results of this study evidence that the coherence is built for besides the linguistic elements, being linked to the interaction. In a global vision, the title maintains relationship with the news and comments of the peoples form a logical sequence inside of the own hypertext that, at the same time, it depends on communicative intentions and elements extralinguistics to produce sense